Glibenclamide Attenuates Neuroinflammation and Promotes Neurological Recovery After Intracerebral Hemorrhage in Aged Rats - Jiang, Bing; Zhang, Ying; Wang, Yan; Li, Zheng; Chen, Qianwei; Tang, Jun; Zhu, Gang (Frontiers in Aging Neuroscience, 2021)
Intracerebral hemorrhage (ICH) is a common disease in elderly populations. Inflammation following ICH plays a detrimental role in secondary brain injury, which is associated with the poor prognosis of ICH patients, and no efficient pharmacological preventions are available. Here, we investigated the effects of glibenclamide (GLC) on neuroinflammation in an autoblood-induced aged rat (18 months old) model of ICH. Rats were randomized into the sham, vehicle and GLC groups. First, we investigated the expression level of sulfonylurea receptor 1 (Sur1) surrounding the hematoma after ICH. Then, neurological scores were calculated, and water maze tests, brain water content analysis, western blotting and immunofluorescence assays were to detect the neuroprotective effect of GLC. The expression of the Sur1-Trpm4 channel was significantly increased in the perihematomal tissue following ICH in aged rats. GLC administration effectively reduced brain edema and improved neurofunction deficits following ICH. In addition, GLC increased the expression of brain-derived neurotrophic factors and decreased the expression of proinflammatory factors (TNF-α，IL-1 and IL-6). Moreover, GLC markedly reduced Ikappa-B (IκB) kinase (Ikk) expression in microglia and NF-κB-P65 levels in perihematomal tissue. GLC ameliorated ICH-induced neuroinflammation and improved neurological outcomes in aged rats. GLC exert these effects, in part, by regulating the NF-κB signaling pathway through the Sur1-Trpm4 channel.